The 18S–25S ribosomal RNA unit of yerba mate (Ilex paraguariensis A. St.-Hil.) - Aguilera, Patricia Mabel; Grabiele, Mauro; Debat, Humberto Julio; Bubillo, Rosana Elizabeth; Martí, Dardo Andrea (2018)
We present the first report of the transcribed 18S–25S ribosomal DNA (rDNA) unit of the South American crop Ilex paraguariensis. This tree is consumed as an infusion named “mate”. Next-generation sequencing data were assembled, reference-annotated and further characterized. The assembled consensus sequence of the complete transcribed rDNA unit is 6961 nt, with a coverage of ∼18,646X and 99.3% of global sequence similarity. The transcribed 18S and 25S rDNA genes of yerba mate are the first in the genus to be characterized, combined with the 5.8S that is identical to the consensus sequence of Ilex. The ITS1 and the ITS2 display species-specific regions, useful to differentiate yerba mate from adulterant taxa of the manufactured product. A replication slippage process seems significant in the evolution of the internal transcribed spacer in Ilex. The 5-external transcribed spacer consists of SR1, which encloses a large inverted repeat/hairpin region, and SR2, which is a high homology region in the Asterids clade and embrace six distinctive inverted repeat/hairpin segments. The 3ETS presents a pyrimidine-rich block associated with transcription termination, mirror-like palindromes and repetitive segments, all networking at the secondary structure level. This information will be helpful in carrying out future studies in the molecular evolution characterization of this crop and related species of Ilex.